The Influence Of Discount Framing And Peer Influence On Cosmetic Purchase Decisions In Tiktok Commerce: The Moderating Role Of AI-Based Recommendations - Anggraeni Pratama Indrianto; Ikhsan Nurahman; Dani Taupan Ramdani; Muhammad Artova Al-Kindi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores how discount framing and peer influence affect consumers' purchase decisions for cosmetic products on TikTok, and whether AI-based recommendations strengthen these effects. As TikTok Shop continues to grow as a popular social commerce platform in Indonesia, understanding the role of marketing strategies and user interactions becomes increasingly important. The research uses a quantitative approach, involving 200 female TikTok users aged 26–35 in the Greater Jakarta area who have purchased cosmetics through the platform. Data were analyzed using Structural Equation Modeling (SEM). The results show that both discount framing and peer influence have a significant positive impact on purchase decisions. Additionally, AI recommendations were found to play a moderating role, increasing the effectiveness of both factors when product suggestions matched user preferences. These findings suggest that combining clear discount offers, social influence, and personalized product recommendations can improve consumer buying behavior in the online beauty market. Keywords: TikTok Shop, discount framing; peer influence, AI recommendations, purchase decisions, cosmetic products, social commerce.